A Hybrid Implementation Model to Develop Cooperative Controllers for Team-Based Operations of UAV/AUS-MAUVs Group - Ngo, Van Hien (Old Journal, 2018)
A novel hybrid control model is proposed to implement cooperative controllers, which permit an Unmanned Aerial Vehicle (UAV) coordinated with the Autonomous Unmanned Ship/Multiple Autonomous Underwater Vehicles (AUS/MAUVs) team to effectively perform missions of ocean exploration in the wide range. This model is based on hybrid automata and the Real-Time Unified Modeling Language (Real-Time UML) for capturing the whole development lifecycle of cooperative controllers. The paper shows out stepwise the main research contents as follows: the coordinated structure and scenarios are define to gather the requirements of control analysis; hybrid automata’s features are specialized to model the coordination behaviors of UAV/AUS-AUVs; the real-time communication pattern is created by using the ‘capsules, ports and protocols’ notation of Real-Time UML for depicting in detail the design components. The detailed design components are then converted into the implementation model by using open-source platforms such as OpenModelica in order to quickly simulate the cooperative controller. Following this proposed model, a cooperative controller permits a quadrotor UAV combined with a pair of small-scale AUS/03-AUVs to perform pre-determined search scenarios with the coordination mechanisms for ocean exploration, was designed and simulated with good reliability and feasibility.